xylP Promoter-Based Expression System and Its Use for Antisense Downregulation of the Penicillium chrysogenum Nitrogen Regulator NRE - Zadra, Ivo; Abt, Beate; Parson, Walther; Haas, Hubertus (Applied and environmental microbiology, 2000)
A highly inducible fungal promoter derived from the Penicillium chrysogenum endoxylanase ( xylP ) gene is described. Northern analysis and the use of a β-glucuronidase ( uidA ) reporter gene strategy showed that xylP expression is transcriptionally regulated. Xylan and xylose are efficient inducers, whereas glucose strongly represses the promoter activity. Comparison of the same expression construct as a single copy at the niaD locus in P. chrysogenum and at the argB locus in Aspergillus nidulans demonstrated that the xylP promoter is regulated similarly in these two species but that the level of expression is about 80 times higher in the Aspergillus species. The xylP promoter was found to be 65-fold more efficient than the isopenicillin- N -synthetase ( pcbC ) promoter in Penicillium and 23-fold more efficient than the nitrate reductase ( niaD ) promoter in Aspergillus under induced conditions. Furthermore, the xylP promoter was used for controllable antisense RNA synthesis of the nre -encoded putative major nitrogen regulator of P. chrysogenum . This approach led to inducible downregulation of the steady-state mRNA level of nre and consequently to transcriptional repression of the genes responsible for nitrate assimilation. In addition, transcription of nreB , which encodes a negative-acting nitrogen regulatory GATA factor of Penicillium , was found to be subject to regulation by NRE. Our data are the first direct evidence that nre indeed encodes an activator in the nitrogen regulatory circuit in Penicillium and indicate that cross regulation of the controlling factors occurs.